When the silent child speaks: identity and subversion in Anthony Browne’s voices in the park - Moussa, Maher Ben (Penerbit Universiti Kebangsaan Malaysia, 2023)
By examining the subversive discourse of both children, Charles and Smudge, this paper will focus on the child’s identity in Anthony Browne’s postmodern picture book Voices in the Park. Drawing on the postmodern theory and mainly on Lyotard’s perception of childhood as a time of intense creativity and imagination, where the child is free to explore the world in a way that is not bound by the adult’s rationality and logic, this paper will analyse how Charles’s and Smudge’s discourses dare to go against the normative discourse of their parents. Smudge manages to change her father’s discourse, while Charles deconstructs his mother’s discourse by exposing its flaws and creating the possibility for resistance. By analysing the underlying tensions between the normative discourses of the parents and that of the children, which Lyotard calls the ‘other of all discourse’, this study offers some insights into the identity of the child Browne presents to his readers. This paper highlights the nature of the agency the children manage to construct through their encounters in the park. It will conclude that although children are an integral part of the parents’ normative power structure, they manage to become a disruptive force of change from within the system itself.